Permanent Capital Losses after Banking Crises - Baron, Matthew; Laeven, Luc; Pénasse, Julien; Usenko, Yevhenii (Quarterly Journal of Economics, 2026)
Abstract We study the mechanisms driving bank losses across historical banking crises in 46 economies and the effectiveness of policy interventions in restoring bank capitalization. We find that bank stocks experience large, permanent declines at the onset of crises. These losses predict commensurate long-term declines in banks’ earnings and dividends, rather than elevated future equity returns. Bank losses are primarily driven by write-downs of nonperforming assets, not asset sales during panics. Forceful liquidity-based interventions during crises predict only small, temporary increases in bank market value. Overall, these results suggest that bank losses during crises are not primarily due to temporary price dislocations. Early liquidity interventions can avert banking crises, but only under specific conditions. Once large bank equity declines have occurred, policy responses have historically failed to prevent persistent undercapitalization in the banking sector.